2004
DOI: 10.1111/j.1745-7599.2004.tb00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Nondaily Hormonal Contraception: Considerations in Contraceptive Choice and Patient Counseling

Abstract: Despite the efficacy of OCs, missed pills are quite common and contribute to unintended pregnancy. Many women in all population categories would benefit from the convenience and reliability of nondaily hormonal contraceptives. The highest efficacy rates with typical use are associated with agents that require minimal user participation (i.e., Depo-Provera, Mirena). Compared to daily regimens, all nondaily options offer increased convenience and may contribute to improved patient adherence. However, barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…[32][33][34] In addition, less restrictive, evidencebased criteria for intrauterine contraception candidate selection should be developed and promoted. 35 Clinical training is also necessary, especially to alleviate concerns about perforations from postpartum insertions or expulsions from incorrect placement in postabortion insertions. 35 Clinical training is also necessary, especially to alleviate concerns about perforations from postpartum insertions or expulsions from incorrect placement in postabortion insertions.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] In addition, less restrictive, evidencebased criteria for intrauterine contraception candidate selection should be developed and promoted. 35 Clinical training is also necessary, especially to alleviate concerns about perforations from postpartum insertions or expulsions from incorrect placement in postabortion insertions. 35 Clinical training is also necessary, especially to alleviate concerns about perforations from postpartum insertions or expulsions from incorrect placement in postabortion insertions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this method overcomes the problem of the oral route (forgetting a pill), or of the possible displacement of IUDs, and it requires less intervention, a benefit particularly useful to women with busy lifestyles who are also in need of a discreet contraceptive method. Moreover, it could be widely appreciated by women who prefer avoiding the discomfort of menstrual cycle, and by women who have recurring menstrual problems, such as dysmenorrhea, endometriosis, and headache [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In such context, the role of the HCP/gynecologist becomes crucial in providing exhaustive information on the medical and technical aspects of all the contraceptive options available and especially in addressing his/her patient's need in line with her current lifestyle and social and cultural environment. Moreover, given the extremely personal nature of the woman's sexual sphere, the dialogue on contraceptive issues is very sensitive and may facilitate the trust in the patient-doctor relationship on many aspects including the medical information provided [20].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects were similar to those of Depo-Provera and included weight gain, menstrual irregularity, headaches, and breast tenderness, although adverse effects were fewer than in trials with DMPA alone. 76,77 A general acceptance of and overall satisfaction with Lunelle by women in clinical trials suggested that this method was widely accepted, but its return into the market is not expected in the future.…”
Section: Injectable Hormonal Contraceptionmentioning
confidence: 99%